Detection of the Bladder Tumor With 3D Ultrasound and Virtual Sonographic Cystoscopy - Kocakoc, E.; Kiris, A.; Orhan, I.; Poyraz, A.; Artas, H.; Firdolas, F. (Amer Roentgen Ray Soc, 2007)
[Abstract Not Available]